The use of non-local Leucanthemum vulgare seeds in the course of restoration measures can no longer be detected several years after their application - Jutta Reiker (PANGAEA, 2023)
Ecological restoration along roadside verges and on compensatory sites requires large-scale reintroductions of plants in form of seeds or seedlings; however, the genetic basis of seed or seedling sourcing is a controversial issue. Formerly, non-local seed sourcing of naturally occurring herbaceous species was common practice. Lately local provenancing got wide attention, and additional strategies are being recommended. All of these, however, raise the costs for restoration efforts. Here we test whether the earlier introduction of non-local seeds of Leucanthemum vulgare agg. in the course of ecological restoration can still be detected several years after the measure. The results are used to provide conservation recommendations for this widespread herbaceous insect-pollinated species. We analyzed the population genetic pattern (AFLP) of the ox-eye daisy in Central Germany on sites formerly restored with non-local seed sources (R) and compared these to the ones of indigenous populations (I). All populations of Leucanthemum vulgare agg. were genetically diverse and did not clearly distinguish between R and I sites. Furthermore, no clear evidence of distinct local genetic patterns was observed. Based on our results, we argue for the use of non-native seeds in the course of restoration measures for ox-eye daisies due to cost savings, but support the demand for a broader population genetic monitoring in order to put the entire system of seed provenance on a solid empirical basis.
Supplement to: Reiker, J (in review): The use of non-local Leucanthemum vulgare agg. seeds in the course of restoration measures can no longer be detected several years after their application. Plant Biology